The religious right a reference handbook - Utter, Glenn H.; Storey, John W. (John Woodrow), 1939- (Millerton, NY : Grey House Pub., 2007)
Examines the religious right and its influence on our government, citizens, society, and politics. Offers a critical historical survey of the religious right movement, focusing on its increased involvement in the political arena, attempts to forge coalitions, and notable successes and failures.
6. Directory of organizations -- Organizations in favor of the Religious Right -- Organizations critical of the Religious Right -- 7. Suggested readings -- Works about the Religious Right -- Biographies -- Religious studies -- The Religious Right and politics -- Works from the Religious Right -- The Religious Right worldview -- Political and economic issues -- Personal and family topics -- Millenarianism -- Periodicals from Religious Right organizations -- 8. Selected multimedia resources -- Multiple formats -- DVDs -- Videotapes -- Audiotapes -- CD-ROMs -- Radio and television programs -- Internet resources -- Glossary -- Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Religious right -- United States; Christianity and politics -- United States; Religious right -- United States -- Bibliography; Christianity and politics -- United States -- Bibliography; RELIGION -- Christianity -- History; Electronic books